Development of box packages time delayer / Salahuddin Imran - Imran, Salahuddin (2024)
A parcel sorting center is usually a huge building that is not open to the public. Mail that needs to be sorted into the right areas is delivered and then the workers at the center will categorize and sort according to the last few lines of the address such as in a country, state, area and more. You may find that your parcel that is only going a few streets away is still delivered to a sorting center first. This might seem unintuitive to you, but it is often the best way for postal services to make sure that their routes are efficient. Everything is sent to huge centers, and then distributed from there. This is the best way for these systems to work and ensure that their service remains efficient for everyone.